Role of splenectomy in patients with hepatocellular carcinoma and hypersplenism. Issue 11 (17th September 2012) - Kim, Sung Hoon; Kim, Do Young; Lim, Jin Hong; Kim, Seung Up; Choi, Gi Hong; Ahn, Sang Hoon; Choi, Jin Sub; Kim, Kyung Sik
Abstract: Introduction: Hypersplenism with thrombocytopenia is a common complication of cirrhosis with portal hypertension. We evaluated the role of splenectomy in patients with hepatocellular carcinoma (HCC) in terms of the improvement of biochemical indices and liver volume. Methods: Nineteen patients with HCC underwent liver resection and splenectomy from January 2000 to December 2009. Thirty‐nine patients who underwent liver resection during the same period were enrolled as case‐matched controls. We performed a retrospective review of prospectively collected data. We analysed the results of biochemical tests, disease‐free survival and overall survival and measured the liver volume before and at 90 days after operation. Results: Preoperative white blood cell counts ( P = 0.001), platelet counts ( P = 0.021), total bilirubin ( P ≤ 0.001) and prothrombin time by international normalized ratio ( P = 0.043) were significantly different. However, these results had converged to similar levels 90 days after the operation. The degree of increment in liver volume were similar ( P = 0.763). In splenectomy group, portal vein thrombosis developed in eight patients and all patients except one recovered using only conservative treatments. There was an operative mortality because of liver failure by thrombosis. Conclusions: Although splenectomy may induce thrombosis, liver failure and subsequent mortality, splenectomy may improve liver function and expand the indication of liver resection if postoperative management is conducted conservatively.